Clustering phenomena in quenched Al, Al–Mg, Al–Si and Al–Mg–Si alloys. (1st March 2020) - Liu, Meng; Guo, Qianning; Zhang, Xingpu; Wüstenhagen, Manuel; Čížek, Jakub; Banhart, John
Abstract: Vacancy and solute atom clusters of various sizes and number densities may be formed in Al alloys during natural ageing (NA) after solutionising and quenching. We study the clustering characteristics of a series of Al–Mg–Si alloys and discuss ageing mechanisms as a function of solute content: in alloys low in Mg (i.e. <0.1 at.%), vacancies tend to aggregate during quenching and subsequently assist the formation of Si-rich clusters in the course of NA. For alloys with higher Mg contents (>0.1 at.%), clustering is initially governed by Si atoms and then by Mg as NA proceeds. Graphical abstract: Image, graphical abstract